2023
DOI: 10.1007/s00784-023-04867-w
|View full text |Cite
|
Sign up to set email alerts
|

Local gingival crevicular fluid, synovial fluid, and circulating levels of prolactin hormone in patients with moderately active rheumatoid arthritis and stage III and IV periodontitis before and after non-surgical periodontal treatment—a controlled trial

Abstract: Objectives We aimed to investigate prolactin (PRL) levels in gingival crevicular fluid (GCF), synovial fluid, and serum in patients suffering from moderately active rheumatoid arthritis (RA) with and without periodontitis (P). Further, to evaluate the effect of non-surgical periodontal treatment on these levels compared to controls. Materials and methods Eighty subjects were divided into 4 groups: group 1: 20 patients with RA + P, group 2: 20 periodontitis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 43 publications
0
1
0
Order By: Relevance
“…However, the effect of menopause on serum prolactin levels is not fully understood, as a result of various age-related mechanisms (38). As in the study of el-Wakeel et al (39), a positive correlation between serum prolactin levels and clinical periodontal parameters (PI, GI, PD, and AL) was found in the present study, indicating the effect of inflammatory diseases and, thus, clinical utility as a biomarker for disease activity and prognosis (39).…”
Section: Discussionsupporting
confidence: 67%
“…However, the effect of menopause on serum prolactin levels is not fully understood, as a result of various age-related mechanisms (38). As in the study of el-Wakeel et al (39), a positive correlation between serum prolactin levels and clinical periodontal parameters (PI, GI, PD, and AL) was found in the present study, indicating the effect of inflammatory diseases and, thus, clinical utility as a biomarker for disease activity and prognosis (39).…”
Section: Discussionsupporting
confidence: 67%
“…In the synovial fluid, RA patients undergoing NSPT present a reduction of prolactin [119]. At the salivary level, a reduction of RANKL was detected [70].…”
Section: The Effect Of Non-surgical Periodontal Treatment (Nspt) On R...mentioning
confidence: 93%
“…NSPT affects the levels of proinflammatory cytokines and various inflammatory mediators in serum, gingival crevicular fluid (GCF), saliva, and synovial fluid in RA-patients (Table 3). In serum, reduction of the following cytokines was observed: TNF-α, IL-6, receptor activator of nuclear factor-KB ligand (RANKL), carbamylated protein (CarP), neutrophil extracellular traps (NETs), the apoptosis inhibitor survivin, and the neuroendocrine hormone prolactin [70,[98][99][100]115,[117][118][119]. RANKL is expressed by stromal cells and osteoblasts to regulate osteoclastogenesis; its dysregulation has been correlated with osteoporosis, bone cancer, and RA [134].…”
Section: The Effect Of Non-surgical Periodontal Treatment (Nspt) On R...mentioning
confidence: 99%
See 1 more Smart Citation
“…More than that the endocrine role of hormones like corticosteroids, androgens, estrogens, and progesterone has also proved a key factor in the formation of gingival pocketing through multiple channels such as clampdown immunity, aggravating exudation, osseous resorption progression and enhancing the fibroblastic action, terminating into clinical attachment loss and presenting periodontal pathology. 10 Mohammed LJ et al reported a high prevalence of 21% of periodontal pathologies in women who were using oral contraceptives compared to only 9% prevalence in the controls who were not using these varieties of steroids. 11 …”
Section: Introductionmentioning
confidence: 99%